Biological photovoltaics: intra- and extra-cellular electron transport by cyanobacteria. (21st November 2012) - Bradley, Robert W.; Bombelli, Paolo; Rowden, Stephen J.L.; Howe, Christopher J.
Abstract : A large variety of new energy-generating technologies are being developed in an effort to reduce global dependence on fossil fuels, and to reduce the carbon footprint of energy generation. The term 'biological photovoltaic system' encompasses a broad range of technologies which all employ biological material that can harness light energy to split water, and then transfer the resulting electrons to an anode for power generation or electrosynthesis. The use of whole cyanobacterial cells is a good compromise between the requirements of the biological material to be simply organized and transfer electrons efficiently to the anode, and also to be robust and able to self-assemble and self-repair. The principle that photosynthetic bacteria can generate and transfer electrons directly or indirectly to an anode has been demonstrated by a number of groups, although the power output obtained from these devices is too low for biological photovoltaic devices to be useful outside the laboratory. Understanding how photosynthetically generated electrons are transferred through and out of the organism is key to improving power output, and investigations on this aspect of the technology are the main focus of the present review.